KAJIAN WISATA BAHARI DI KAWASAN TUREDAWOLA WALO KABUPATEN NIAS UTARA - Meniato Telaumbanua dan M. Baiquni (Jurnal Kawistara, 2015)
The objectives of the research consisted of: (1) to identify the predominance of marine tourism activitiesand attractions in Turedawola Walo; (2) to analyze the degree of significance of activities and attractions,amenities, accessibility, local community conditions, safety, cleanliness and tourism information variablessimultaneously and partially toward Turedawola Walo marine tourism quality; and (3) to examine thedifferences between direct and indirect participation of local community in the case of TuredawolaWalo marine tourism development in North Nias Regency. This research was conducted in the villageof Afulu, Afulu District, North Nias Regency by using a descriptive quantitative research methodwith the questionnaire addressed to 63 tourist/excursionist respondents and 80 local communitiesrespondents used as samples. The results obtained were then processed and analyzed by using multiplelinear regressions analysis to evaluate the significance and prove written hypotheses simultaneouslyand partially of seven factors affecting Turedawola Walo marine tourism quality and Mann-Whitneytest to evaluate the differences between direct and indirect participation of local community in the caseof Turedawola Walo marine tourism development. Results of the research indicated that: (1) the mostpredominant activities and tourist attractions in Turedawola Walo is surfing; (2) amenities, cleanlinessand tourist information variables did not give significant contribution to the quality of Turedawola Walomarine tourism, while activities and attractions, accessibility, local community conditions, and tourismsafety variables gave significant contribution to the quality of Turedawola Walo marine tourism; and (3)indirect participation greater than direct participation of local communities indicated that the majorityof local community in Afulu village participated indirectly in the case of Turedawola Walo marinetourism development in North Nias Regency.